MCU-Dependent mROS Generation Regulates Cell Metabolism and Cell Death Modulated by the AMPK/PGC-1α/SIRT3 Signaling Pathway - Wang, Yuxin; Li, Xiang; Zhao, Fengchao (Frontiers in Medicine, 2021)
The mitochondrial calcium uniporter is an intensively investigated calcium channel, and its molecular components, structural features and encoded genes have long been explored. Further studies have shown that the mitochondrial calcium unidirectional transporter (MCU) is a macromolecular complex related to intracellular and extracellular calcium regulation. Based on current understanding, the MCU is crucial for maintaining cytosolic Ca2+ (cCa2+) homeostasis by modulating mitochondrial Ca2+ (mCa2+) uptake. The elevation of MCU-induced calcium levels is confirmed to be the main cause of mitochondrial reactive oxygen species (mROS) generation, which leads to disordered cellular metabolic patterns and cell death. In particular, in an I/R injury model, in cancer cells, and adipocytes, MCU expression is maintained at high levels. As is well accepted, the AMPK/PGC-1α/SIRT3 pathway is believed to have an affinity for mROS formation and energy consumption. Therefore, we identified a link between MCU-related mROS formation and the AMPK/PGC-1α/SIRT3 signaling pathway in controlling cell metabolism and cell death, which may provide a new possibility of targeting the MCU to reverse relevant diseases.